Combined treatment with Sigma1R and A2AR agonists fails to inhibit cocaine self-administration despite causing strong antagonistic accumbal A2AR-D2R complex interactions: the potential role of astrocytes - Borroto-Escuela, Dasiel O.; Lopez-Salas, Alexander; Wydra, Karolina; Bartolini, Marco; Zhou, Zilong; Frankowska, Malgorzata; Suder, Agata; Benitez-Porres, Javier; Romero-Fernandez, Wilber; Filip, Malgorzata; Fuxe, Kjell (Frontiers in Molecular Neuroscience, 2023)
Previous work indicated that acute treatment with the monoamine stabilizer OSU-6162 (5 mg/kg) via its high affinity for the Sigma1R, significantly increased the density of accumbal shell D2R-Sigma1R and A2AR-D2R heteroreceptor complexes following cocaine self-administration. Ex vivo actions of the A2AR agonist CGS21680 also suggested the existence of enhanced antagonistic accumbal A2AR-D2R allosteric interactions after treatment with OSU-6162 in cocaine self-administration. However, the three days treatment with OSU-6162 (5 mg/kg) failed to alter the behavioral effects of cocaine self-administration. To test these results and the relevance of OSU-6162 (2.5 mg/kg) and/or A2AR (0.05 mg/kg) agonist interactions, treatment with these low doses of the receptor agonists were performed in cocaine self-administration and neurochemical and behavioral effects studied. No effects were demonstrated on cocaine self-administration but marked and highly significant increases using proximity ligation assay (PLA) were induced by the co treatment on the density of the A2AR-D2R heterocomplexes in nucleus accumbens shell. Significant decreases in the affinity of the D2R high and low affinity agonist binding sites were also observed. Thus, in low doses the highly significant neurochemical effects observed upon cotreatment with A2A and Sigma1R agonists on the A2AR-D2R heterocomplexes and their enhancement of allosteric inhibition of D2R high affinity binding are not linked to modulation of cocaine self-administration. The explanation may be related to an increased release by cocaine self-administration of ATP and adenosine from astrocytes in nucleus accumbens shell. This can lead to an increased activation of the A1R protomer in a putative A1R-A2AR-D2R complex modulating glutamate release in the presynaptic glutamate synapse. The hypothesis is introduced that integration of changes in presynaptic glutamate release and post junctional heteroreceptor complex signaling where D2R plays a key role, can lead to absence of changes in the firing of the GABA anti-reward neurons, followed by the absence of reduction of cocaine self-administration in the present experiments.